966 IMPROVING COMMUNICATION WITH RELATIVES IN THE COVID ERA - DEVELOPMENT OF A NEW SERVICE STANDARD. (14th June 2022) - Hough, S; Alićehajić-Bečić, Ð; Pederson, A; Jordan, T; Sharif, F; Lakhi, R; Maynard-Connor, E; Knagg, T
Abstract: Background: Quality improvement project undertaken by the Ageing and Complex Medicine team to improve the quality and quantity of communication with patients' relatives. Introduction: Visitation restrictions at RAEI since the onset of the COVID pandemic have created barriers to effective communication between patients' relatives and the medical team. Patients' relatives were frequently receiving poorly structured information, incorrect information, or even no information. This problem was hospital wide and likely to have affected other trusts. It particularly affected elderly care wards, where the cohort of patients were often less able provide their relatives with updates themselves. We therefore agreed a service standard whereby the medical team would provide a medical update via phone to the patients' next of kin within 24 hours of admission followed by twice weekly updates by any member of the wider MDT. Our aim was to improve the quality and quantity of communication with the patients' relatives. Method: So far 6 data capture cycles have seen us implement change in various ways such as utilisation of a white board to highlight when updates are due, a staff feedback survey to highlight barriers to providing the service and a relative feedback survey to evaluate their experience. Results: Compared to baseline data we have seen an improvement in the quantity of relative updates with most cycles. Conclusion: We have improved the quantity of relative updates and embedded it as established culture on Astley ward. Barriers to success include staffing levels, time burden, and low confidence levels amongst junior doctors. Cycle 7 will see implementation of a teaching session for new junior doctor cohorts to improve their confidence. I would like to share our learning and success with the wider hospital and see implementation of the service standard across all wards within the trust.